ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN RUMAH TANGGA DI DESA KOTAYASA MELALUI PENDEKATAN REGRESI LOGISTIK BINER - Agustini Tripena; Yosita Lianawati; Antonius Ary Setyawan (LPPM Poltek ST Paul, 2023)
Kotayasa Village is a village that has the highest number of poor households in Banyumas Regency with 1,662 poor households (78%). This study aims to determine which factors have a significant effect and interpret the binary logistic regression model for poor households in Kotayasa Village. The data used in this research is secondary data from the Office of Social and Community and Village Empowerment in Banyumas Regency. The results showed that the factors that had a significant effect on poor households in Kotayasa Village were electricity, gold savings and livestock. Meanwhile, factors that have no significant effect are sources of drinking water and private vehicles. The results of the analysis obtained the odds ratio values, namely electric power of 3,999, gold deposits of 7,963, and livestock of 1,497. The electric power variable shows that households with electric power less than equal to 900 have a greater chance of being included in poor households of 3,999. The gold savings variable is that households that do not have gold savings have a greater chance of being included in poor households of 7,963. The livestock variable shows that households that do not have livestock have a greater chance of being included in poor households of 1,497. Keywords: Odds ratio, binary logistic regression, poor household.